2013
DOI: 10.1002/esp.3418
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modeling of moisture content above an oscillating water table: implications for beach surface moisture dynamics

Abstract: This study examined the influence of tidally‐induced oscillations of the beach water table in regulating beach surface moisture dynamics. A series of laboratory experiments were conducted to assess the influence of hysteresis and transient flow effects on surface moisture variability. The experimental apparatus utilized a column of well‐sorted fine sand partially immersed in a reservoir of water. The water level in the reservoir was raised and lowered via a diaphragm‐metering pump to simulate tidally induced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…To illustrate our approach (see also Namikas et al. , and Schmutz and Namikas, ), Figure shows predicted moisture profiles for three water table depths ( h = 1.0 m, 0.4 m and 0.1 m), all with w res = 2 % , w sat = 25 % , α = 3.5 m −1 and n = 3.19, where the latter two values were based on Tuller and Or (). For h = 1.0 m (Figure a) the moisture profile contains an approximately 0.10–0.15 m thick capillary fringe false(wswsatfalse) and a roughly 0.5 m thick layer where the moisture content gradually reduces to w res .…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…To illustrate our approach (see also Namikas et al. , and Schmutz and Namikas, ), Figure shows predicted moisture profiles for three water table depths ( h = 1.0 m, 0.4 m and 0.1 m), all with w res = 2 % , w sat = 25 % , α = 3.5 m −1 and n = 3.19, where the latter two values were based on Tuller and Or (). For h = 1.0 m (Figure a) the moisture profile contains an approximately 0.10–0.15 m thick capillary fringe false(wswsatfalse) and a roughly 0.5 m thick layer where the moisture content gradually reduces to w res .…”
Section: Methodsmentioning
confidence: 98%
“…Here, hysteresis effects with higher surface moisture content with falling than rising tide for the same water table depth may be substantial. This was illustrated from laboratory experiments with a vertical sand (130 μ m) column and an oscillating water table (Schmutz and Namikas, ) and from field measurements on an upper beach (also 130 μ m; Padre Island National Seashore, USA) under spring tidal conditions when the groundwater depth was less than about 1 m (Schmutz, ). It is likely that the importance of hysteresis to surface moisture variability diminishes with increasing grain size (e.g., Yang et al.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…[] observed strong hysteresis effects near a fluctuating capillary fringe with different flux and pressure boundary conditions, and water content varied more in the case of slow fluctuation. Schmutz and Namikas [] measured the surface moisture content above an oscillating water table and simulated the response of surface water content to water table oscillation using the Hydrus‐1D program [ Simunek et al ., ] with both hysteresis and nonhysteresis approaches. Comparisons between measured and simulated surface water content showed that hysteresis exerts significant influence on surface moisture content dynamics, especially when the water table is close to land surface.…”
Section: Introductionmentioning
confidence: 99%
“…To study moisture, Robin and his students (I. Delgado-Fernandez and I. Darke) designed innovative methods to quantify moisture (e.g. Darke et al, 2009;Delgado-Fernandez et al, 2009).In this collection, Edwards and Namikas (2013) introduce an infrared sensor to measure beach surface moisture, and Schmutz and Namikas (2013) examine the influence of tidal oscillations of the water table and the relationship with beach moisture.…”
mentioning
confidence: 99%